Air pollution and its governing legal administrative mechanisms in Iraq - Abdulkadhim, Asmaa; Md Dahlan, Nuarrual Hilal; Abdul Rahman, Rohana (IISTE, 2017)
Iraq has had a big share of air pollution due to industrial development taking place in the country.To address the air pollution issues in Iraq, the government has passed some important environmental legislations, such as the Act of Ministry of Environment in 2008, the Act of Protect and Improve Environment in 2009, and the Order of Air Protection in 2012 with a few international environmental responsibilities. These legislations consist of mechanisms allowing administration to use it in order to maintain air quality.This paper discusses the executive mechanisms:- preventive and curative to maintain air quality by utilizing the existing legal system tools.Further, to give an explanation for the sources of air pollutants in Iraq.It relies on primary sources namely, in-depth interview with participants in different criteria such as the professionals including experts, academics and supported with secondary sources.